PARENTAL ALIENATION SYNDROME IN THE LEGISLATION OF THE MEXICAN REPUBLIC - Sanchez, Gabriela Santiago; Hernandez, Francisca Silva; Prats, German Martinez (IJRDO - Journal of Social Science and Humanities Research, 2021)
The legislation of Tabasco and in other states in review of their reforms is not established the figure of parental alienation, leaving a lag in the defense of the minor in the civil or family system of the State. The parental alienation syndrome causes conflict in the process of separation or end of marriage in case of having children, being they the main affected in this process. Therefore, the interest in addressing and describing the laws of the Mexican state regarding parental alienation.